Characterization of the Tubovesicular Network in Plasmodium vivax Liver Stage Hypnozoites and Schizonts - Sylvester, Kayla; Maher, Steven P.; Posfai, Dora; Tran, Michael K.; Crawford, McKenna C.; Vantaux, Amélie; Witkowski, Benoît; Kyle, Dennis E.; Derbyshire, Emily R. (Frontiers in Cellular and Infection Microbiology, 2021)
Plasmodium is a genus of apicomplexan parasites which replicate in the liver before causing malaria. Plasmodium vivax can also persist in the liver as dormant hypnozoites and cause clinical relapse upon activation, but the molecular mechanisms leading to activation have yet to be discovered. In this study, we use high-resolution microscopy to characterize temporal changes of the P. vivax liver stage tubovesicular network (TVN), a parasitophorous vacuole membrane (PVM)-derived network within the host cytosol. We observe extended membrane clusters, tubules, and TVN-derived vesicles present throughout P. vivax liver stage development. Additionally, we demonstrate an unexpected presence of the TVN in hypnozoites and observe some association of this network to host nuclei. We also reveal that the host water and solute channel aquaporin-3 (AQP3) associates with TVN-derived vesicles and extended membrane clusters. AQP3 has been previously shown to localize to the PVM of P. vivax hypnozoites and liver schizonts but has not yet been shown in association to the TVN. Our results highlight host-parasite interactions occur in both dormant and replicating liver stage P. vivax forms and implicate AQP3 function during this time. Together, these findings enhance our understanding of P. vivax liver stage biology through characterization of the TVN with an emphasis on the presence of this network in dormant hypnozoites.